Iguratimod ameliorates bleomycin‐induced alveolar inflammation and pulmonary fibrosis in mice by suppressing expression of matrix metalloproteinase‐9. (21st January 2019) - Zhao, Like; Mu, Bingyao; Zhou, Rongwei; Cheng, Yongjing; Huang, Cibo
Abstract: Aim: To investigate the potential therapeutic efficacy of iguratimod (IGU) on bleomycin (BLM)‐induced pulmonary fibrosis in mice. Methods: A total of 75 C57BL/6 mice were randomly and evenly divided into control group, BLM (5 mg/kg) group, BLM + IGU (90 mg/kg) group, BLM + methylprednisolone (MP, 10 mg/kg) group and BLM + pirfenidone (PF, 100 mg/kg) group. The mice were sacrificed on day 7, 14 and 28. The lung tissue was examined by hematoxylin and eosin staining and Masson staining to evaluate the degree of alveolitis and fibrosis, and serum cytokines were measured. Results: Histopathological results showed that IGU attenuated BLM‐induced alveolar inflammation and decreased collagen deposition in lung tissue from day 7 till day 28. Both the pathological alveolitis and fibrosis scores in the drug‐treated groups (IGU group, MP group and PF group) were decreased dramatically compared with the BLM group on day 7, 14 and 28 ( P < 0.05). There were no statistical significances among these three groups. Cytokine profile showed that IGU decreased the level of tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1, IL‐6 and matrix metalloproteinase (MMP)‐9 which were up‐regulated by BLM on day 7, 14 and 28 ( P < 0.05). Furthermore, there is a strong correlation between the severity of pulmonary fibrosis and serum MMP‐9 levels. Conclusion: IGU can decrease BLM‐induced pulmonary fibrosis, and the anti‐fibrotic effect of IGU is mediated partly via inhibition of MMP‐9, which suggests that IGU could potentially be an effective therapeutic strategy for pulmonary fibrosis.